2016
DOI: 10.1002/rcm.7506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites of the novel anti‐tumor drug candidate MDH‐7 in rat urine by liquid chromatography coupled with triple quadrupole linear ion trap mass spectrometry

Abstract: Based on the profiles of the metabolites, possible metabolic pathways of MDH-7 in rats were proposed for the first time. This study provides new and available information on the metabolism of MDH-7 which is very useful to further understand its in vivo metabolic fate. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The caffeine metabolites in lettuce were identified using the optimized EMS-IDA-EPI scan in LC-QTrap-MS/MS. The EMS-IDA-EPI scan is commonly used to identify metabolites in non-target screening . In this study, eight metabolites derived from caffeine were tentatively identified, which were xanthine, methylxanthine, theobromine, paraxanthine, theophylline, 1,3-dimethyluric acid, 1,3,7-trimethyluric acid (M210), and 8-hydroxy-1,3,7-trimethyl-3,7,8,9-tetrahydro-1H-purine-2,6-dione (M212) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The caffeine metabolites in lettuce were identified using the optimized EMS-IDA-EPI scan in LC-QTrap-MS/MS. The EMS-IDA-EPI scan is commonly used to identify metabolites in non-target screening . In this study, eight metabolites derived from caffeine were tentatively identified, which were xanthine, methylxanthine, theobromine, paraxanthine, theophylline, 1,3-dimethyluric acid, 1,3,7-trimethyluric acid (M210), and 8-hydroxy-1,3,7-trimethyl-3,7,8,9-tetrahydro-1H-purine-2,6-dione (M212) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The EMS-IDA-EPI scan is commonly used to identify metabolites in non-target screening. 43 In this study, eight metabolites derived from caffeine were tentatively identified, which were xanthine, methylxanthine, theobromine, paraxanthine, theophylline, 1,3-dimethyluric acid, 1,3,7-trimethyluric acid (M210), and 8-hydroxy-1,3,7-trimethyl-3,7,8,9-tetrahydro-1H-purine-2,6-dione (M212) (Table S3). Among these eight metabolites, the commercially available authentic standards xanthine, 3-methylxanthine, 7-methylxanthine, theobromine, paraxanthine, theophylline, and 1,3-dimethyluric acid were used to confirm the metabolites in lettuce shoots based on the European Union Guideline 2002/657/EC.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%